In vitro basal and metabolism-mediated cytotoxicity of flavonoids - Soares, VCG; Varanda, Eliana Aparecida [UNESP]; Raddi, MSG (Elsevier B.V., 2006)
The purpose of this study was to compare the basal cytotoxicity and metabolism-mediated cytotoxicity of kaempferol, quercetin and rutin. McCoy cells were exposed to various concentrations of the flavonols with and without the S9 system. The neutral red uptake assay was used to determine viability after 24 h at 35-37 degrees C. Dose-response curves were established for each flavonol in the presence and absence of external metabolizing systems. Kaempferol and quercetin were cytotoxic and provoked a dose-dependent decrease in cell viability, without the S9 system. The hepatic S9 microsomal fraction metabolized these compounds to less cytotoxic metabolites. In contrast, rutin at 500 mu g/ml failed to produce any overt signs of toxicity in either assay. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: flavonols; cytotoxicity; S9; metabolic activation